Translation Techniques Analysis on The Story of Selera Nusantara Mobile Video Game - Muhamad Hardiyanto Kiyai Mardjo; Novriyanto Napu; Sri Widyarti Ali (TRANSBAHASA, 2025)
This study aims to analyze the translation techniques used in the English version of Selera Nusantara, a mobile video game developed by Gambir Game Studio that highlights Indonesia’s culinary and cultural richness. The research focuses on Season 1, Episode 1 of the game, which introduces the main narrative and characters. Using Anthony Pym’s (2018) typology of translation solutions as the analytical framework, this study identifies and categorizes the translation strategies applied in rendering the game’s dialogue and cultural references from Indonesian to English. The research employed a descriptive qualitative method, with data collected through documentation and content analysis of the game’s bilingual scripts. The findings revealed a total of 1,196 translation solutions, with Perspective Change being the most dominant (373 instances), followed by Cultural Correspondence (327) and Density Change (259). The subcategory Relocation of Culture-Specific Referents emerged as the most frequently used strategy within Cultural Correspondence. These results suggested that translators prioritized cultural adaptability and narrative clarity to make the game accessible to a global audience while preserving its Indonesian identity. The study contributed to translation studies by demonstrating the applicability of Pym’s typology to interactive digital content and highlighting the importance of translation in promoting local culture through global media like video games.